Pemanfaatan Limbah Pertanian (Jerami Padi) sebagai Pakan Ternak Jangka Panjang di Dusun Semelek Kabupaten Lombok Timur - Azis, Lalu Khairil; Karmana, I Wayan (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
The purpose of this activity is to utilize agricultural waste as long-term animal feed in Semelek Hamlet, Santong Village, Terara District, East Lombok Regency. The activity methods that have been carried out are: lectures, demonstrations, and exercises. At the implementation stage of this community service, socialization was carried out using the lecture method intended to provide additional knowledge and skills to members of the cattle farming group about the quality of feed from fermented rice straw. Then continued with the demonstration method as well as training in making fermented rice straw using a mixture of urea and fermented rice straw using rice bran, in addition to other mixtures of materials such as EM-4. Demonstrations and exercises carried out by resource persons and participants, namely: 1) making fermented rice straw using a mixture of urea; and 2) making fermented rice straw using a mixture of bran. The results of the lectures, demonstrations, and exercises carried out by the speakers and participants showed that rice straw fermentation can be carried out using two effective methods, namely using a urea mixture and using a bran mixture. In the first method, the urea mixture functions as a source of nitrogen that accelerates the fermentation process and increases the protein content of the straw, while in the second method, the bran acts as an additional energy source for fermentation microorganisms. Both methods succeeded in producing fermented straw that was softer, did not have a pungent odor, and was preferred by livestock compared to ordinary straw. Participants also looked enthusiastic and active in following each stage, from mixing the ingredients to the fermentation storage process, which proved that this activity provided practical experience that was useful for application in the field.